EXPLORING STUDENTS’ STRATEGIES IN LEARNING ENGLISH AT SENIOR SECONDARY SCHOOL - Nurjihan Nabilah Noor; Nurdin Noni; Sukardi Weda; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study explores the strategies used by senior secondary school students in learning English at SMAN 1 Tinambung, West Sulawesi, Indonesia. This study aims to: (1) Identify what strategies are used by XII grade students at SMAN 1 Tinambung (2) What strategies are preferred by XII grade students in learning English and (3) The impact of learning strategies on learning independence, self-confidence, and social interaction of students in learning English. This research is categorized into descriptive qualitative research. This research uses the data triangulation method to obtain the validity of the research results. Data collection was done through three stages: (1) observing in the classroom to observe students' actions in the learning process, (2) conducting in-depth interviews or indept intervieuw to get the topic of information under study, (3) documentation as a supporting tool in compiling this research. The results show that (1) students use Memory strategy, Cognitive strategy, Compensation strategy, Metacognitive strategy, Affective strategy, and Social strategy, (2) students prefer technology-based strategy (social media, internet, AI), entertainment media-based strategy (film, animation, music), vocabulary-focused strategy, and collaborative learning strategy, (3) learning strategies have an impact on students' independence through variations in time management and technology use, increase confidence through psychological techniques and structured exercises, and strengthen social interaction by placing language as a communication tool in authentic contexts.